Mn-substituted goethite for uranium immobilization: A study of adsorption behavior and mechanisms. (July 2020) - Zhang, Xiaowen; Zhang, Lijiang; Liu, Yong; Li, Mi; Wu, Xiaoyan; Jiang, Tianjiao; Chen, Chen; Peng, Ying
Abstract: Goethite is a common iron hydroxide, which can be substituted by manganese (Mn) in the goethite structure. It is important to investigate the immobilization of uranium(VI) on Mn-substituted goethite (Mn-Goe) to understand the fate and migration of uranium in soils and sediments. In this study, the sorption of uranium(VI) by Mn-Goe was investigated as a function of pH, adsorbent dosage, contact time, and initial uranium concentration in batch experiments. Several material analysis techniques were used to characterize manganese substituted materials. Results indicated that Mn was successfully introduced into the goethite structure, the length of particles increased gradually, the surface clearly exhibited higher roughness with increasing Mn content, and that uranium(VI) sorption of synthetic Mn-Goe appeared to be higher than that of goethite. The sorption kinetics supported the results presented by the pseudo-second-order model. The sorption capacity of uranium on Mn-Goe was circa 77 mg g −1 at pH = 4.0 and 25 °C. Fourier transform-infrared spectroscopy (FT-IR) analyses revealed that uranium ions were adsorbed through functional groups containing oxygen on the Mn-Goe structure. The enhancement of Mn-substitution for the uranium(VI) sorption capacity of goethite was revealed. This study suggests that goethite and Mn-Goe can both play a significant role in controlling the mobility and transport of uranium(VI) in the subsurface environment, which is helpful for material development in environmental remediation. Graphical abstract: Image 1 Highlights: Mn-substituted goethite sorption capacity of uranium(VI) was circa 77 mg g −1 . Manganese enhanced the sorption capacity of goethite for uranium(VI) at pH = 4.0. Uranium(VI) adsorption on Mn-Goe10 mainly is an inner-sphere complexation process.